Magnetic Studies of Iron-Doped Probable Weyl Semimetal WTe2 - Andranik S. Khachatryan; Elena V. Charnaya; Marina V. Likholetova; Evgeniy V. Shevchenko; Min Kai Lee; Lieh-Jeng Chang; Sergey V. Naumov; Alexandra N. Perevalova; Elena B. Marchenkova; Vyacheslav V. Marchenkov (Condensed Matter, 2023)
The non-trivial topology of electronic bands in Weyl semimetals originates from band inversion due to strong spin–orbit coupling. The Weyl semimetals have pairs of Weyl gap-less nodes in the bulk Brillouin zone. The tungsten ditelluride WTe2 likely belongs to type II Weyl semimetals. Doping WTe2 with magnetic ions could induce magnetic ordering in this crystal, which provides prospects for practical applications. We studied the magnetic properties of the iron-doped single crystals Fe0.03W0.97Te2, annealed and unannealed, in comparison with the undoped WTe2. Measurements of the dc magnetization were carried out from 1.8 to 400 K. We revealed pronounced ferromagnetic ordering that was affected by annealing. Anomalies associated with antiferromagnetism and paramagnetism were also found. The magnetic order was suppressed by a field of 60 kOe. The rise in susceptibility with increasing temperature was observed at high temperatures in all samples and was treated using a model developed for Weyl semimetals. The Curie–Weiss law fit at 60 kOe showed that the effective magnetic moment was close to that of Fe2+. Metamagnetism was demonstrated for the unannealed doped WTe2 crystal. The data for the heat capacity of the iron-doped sample agreed with results for the undoped WTe2.